2010
DOI: 10.1115/1.4002772
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of the Time-Resolved Heat and Temperature Array

Abstract: The development and evaluation of a differential style heat flux gauge is presented. The sensor is constructed from spot-welded foils of copper and constantan on either side of a thin Kapton polyimide film and is capable of measuring the heat flux and surface temperature at ten locations simultaneously. Analytical modeling was performed to estimate the sensor’s sensitivity and time response. Calibrations were performed in conduction and radiation yielding an average heat flux sensitivity of 20.4 μV/(kW/m2). Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…To minimize the thermal effect of the sensor's presence (less than 0.1 mm total thickness), the remainder of the heated section was masked with the same Kapton used in the sensor construction to maintain uniform smooth surface conditions. Details of the development and calibration of the THeTA are given in Hubble & Diller (2010b) and a depiction of the sensor is given in figure 4. Heat flux through the sensor is proportional to the temperature drop across the thermal barrier as directly measured by two type-T (copper-constantan) thermocouples connected in series ( V 1 ).…”
Section: Water Tunnel Facility and Turbulence Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…To minimize the thermal effect of the sensor's presence (less than 0.1 mm total thickness), the remainder of the heated section was masked with the same Kapton used in the sensor construction to maintain uniform smooth surface conditions. Details of the development and calibration of the THeTA are given in Hubble & Diller (2010b) and a depiction of the sensor is given in figure 4. Heat flux through the sensor is proportional to the temperature drop across the thermal barrier as directly measured by two type-T (copper-constantan) thermocouples connected in series ( V 1 ).…”
Section: Water Tunnel Facility and Turbulence Generationmentioning
confidence: 99%
“…Surface temperature measurements are obtained from the thermocouple located on the top of the THeTA ( V 2 ). Each of the ten sensors on the THeTA was individually directly calibrated by conduction and radiation for the steady-state heat flux sensitivity and by radiation for the transient response, as described by Hubble & Diller (2010b). Because of variations in the thickness during construction, the calibrated sensitivities of each sensor used are somewhat different.…”
Section: Water Tunnel Facility and Turbulence Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Though, the short period maintain thermophilic condition was may be due to the less volume of waste and high surface area for heat loss in small systems as this was agreed (37). Furthermore, the result shown that it had undergone mesophilic bacteria was active during the composting process (38) where it is known to be effective for breakdown of biomaterial and the rise of temperature higher than ambient temperature shows that bacteria work on oxidizable materials in the mixture of compost (39). However, we could saw that there are differences between the compost pile temperature and ambient temperature that this explains that the aerobic process happens.…”
Section: Temperature Between Ambient and Compostmentioning
confidence: 69%
“…This sensor is used Fourier's law, which for 1D steady state, to measure heat flux. Because of the small thermal conductivity and weak high-temperature tolerant of the non-metal thermal resistance, the response speed of the differential sensor is slow and the range is not wide [4,5]. Thus it affects its uses in the high-temperature explosion field.…”
Section: Introductionmentioning
confidence: 99%